Elaine Ward: Indigenous Peoples between Human Rights and Environmental Protection - Based on an Empirical Study of Greenland - Hasager, Ulla (Tidsskriftet Antropologi, 2019)
Elaine Ward: Indigenous Peoples between Human Rights and Environmental Protection - Based on an Empirical Study of Greenland Anmeldes af Ulla Hasager